2009
DOI: 10.1007/s12199-009-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

The current status of hand washing and glove use among care staff in Japan: its association with the education, knowledge, and attitudes of staff, and infection control by facilities

Abstract: Objective Hand hygiene is a basic measure to prevent infections. The purpose of this study was to obtain suggestions for the improvement of hand hygiene by evaluating the education, knowledge, and attitudes of care staff at facilities for the elderly in regard to hand washing and glove use, as well as infection control policies by those facilities. Methods Among a total of 147 special nursing homes and health service facilities for the elderly in Yamaguchi Prefecture, Japan, questionnaires were sent from Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…Ever since workers who are identified the problem of infection acquired in Hospital, at tempts have been made to eradicate or at least reduce rates of acquisition. Hospital acquired infection, also known as nosocomial infection, is defined as an infection for which there is no evidence of its presence or incubation at the time of admission or any infection acquired within 72 hours of admission to Hospital (3,4,5). World Health Organization published a guide to prevent HIV transmission in health facilities.…”
Section: Back Groundmentioning
confidence: 99%
“…Ever since workers who are identified the problem of infection acquired in Hospital, at tempts have been made to eradicate or at least reduce rates of acquisition. Hospital acquired infection, also known as nosocomial infection, is defined as an infection for which there is no evidence of its presence or incubation at the time of admission or any infection acquired within 72 hours of admission to Hospital (3,4,5). World Health Organization published a guide to prevent HIV transmission in health facilities.…”
Section: Back Groundmentioning
confidence: 99%
“…Takahashi et al . found that care staff who were educated about hand washing showed significantly higher adherence than a group who had not been educated 26 . Duggan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Sakihama et al investigated HH practices before patient contact at four teaching hospitals, which demonstrated that the HH adherence rate among nurses was 23% (Sakihama et al, 2016). Preceding literature based on questionnaire reported HH implementation rate at Japanese institutions was approximately 34% (Takahashi et al, 2009), and they had already pointed out a discrepancy between the self-evaluation and actual HH practice (Sakihama et al, 2016). Different from their investigation, the present study targeted only medical wards, but not surgical, intensive-care, and emergency wards.…”
Section: Discussionmentioning
confidence: 99%